A cross sectional study to assess the awareness and practice about cough etiquettes among respiratory symptomatic patients in Tamil Nadu - Shrivastava, Prateek Saurabh; RamBihariLal Shrivastava, Saurabh (International Journal Of Community Medicine And Public Health, 2019)
Background: The emergence of respiratory infections has been attributed to the exposure of human beings to the wide gamut of airborne pathogens. Cough etiquette and respiratory hygiene have been recommended as tools to reduce such transmission. Methods: A cross-sectional descriptive study was conducted among respiratory symptomatic patients attending urban and rural health training centre of a tertiary care hospital for 6 months duration (October 2018 to March 2019) to study their knowledge and practices related to cough etiquettes. A total of 240 study subjects were interviewed face to face with the help of a semi-structured questionnaire after obtaining their written informed consent. The study findings were recorded in an Excel sheet and analysis was done using SPSS version 20. Results: Correct knowledge about cough etiquettes was found in only 22 (9.1%) participants. Almost half of the participants 122 (50.8%) covering mouth and nose with hands while only 14 (9.7%) were using of face mask during bouts of coughing. Barriers to preventive practices were lack of awareness about cough etiquettes and hand hygiene in 14.1% and 66.3%, respectively followed by severity and frequency of bouts of cough in 29 (12.1%) subjects. Conclusions: Knowledge and practice of cough etiquette was not found to be satisfactory in the present study. Thus, it is high time to address this issue and bridge the gap in knowledge as well as practice of cough etiquette among the general population in order to reduce the person to person transmission and thereby decreasing the burden of respiratory infection.